Urban agriculture supports China’s vegetable supply without raising greenhouse gas emissions - Yuanchao Hu; Prajal Pradhan; Haoran Zhang; Zhen Wang; Qianyuan Huang; Qiqi Jia; Xihong Lian; Chao Xu; Rui Yang; Yuxi Tian; Zhibang Xu; Limin Jiao; et al. (Resources, Environment and Sustainability)
Measuring the production potential and environmental sustainability of urban agriculture in developing countries highlights the value of promoting it. We constructed a new dataset of urban productive spaces for 124 large Chinese cities, which includes indoor balconies, rooftops, urban open spaces, and courtyards. In particular, if moderately exploited, approximately 18% of the 13 million rooftops could be planted, considering factors such as building height, age, rooftop slope, occupation, and other restrictions. Applying both greenhouse and open-air cultivation techniques in all the spaces, about 30% (7%–198% across cities) of urban vegetable demand could be met. However, urban agriculture has little potential in greenhouse gas emission mitigation, with the average intensity (0.30 kgCO2e/kg) being similar to traditional agriculture (0.31 kgCO2e/kg), even if several system-wide benefits, such as reduced food miles, were considered. Despite the multiple benefits, conducting urban agriculture requires massive water, substrate, metal, and plastic inputs. We demonstrate that high-tech urban agriculture can have a lower GHG intensity, but it is essential to consider agroclimatic conditions and promote more sustainable practices.